An analysis of predictors for heavy alcohol drinking using nationally representative survey data in Japan - Tasuku Okui (BMC, 2021)
Abstract Background Predictors of heavy or moderate alcohol drinking behavior have not been investigated using recent nationally representative survey data in Japan. This study investigated the effects of the predictors of heavy and moderate alcohol drinking in Japan using nationally representative survey data. Methods Anonymous data from the 2013 Comprehensive Survey of Living Conditions in Japan were used to compare the predictors of heavy and moderate drinkers with those who abstain. Anonymized data that are resampled from all the survey data from the Ministry of Health, Labour and Welfare were obtained. Age group, marital status, living arrangements, educational level, household income, smoking status, and employment type were used as the explanatory variables. In addition, the drinking status (i.e., heavy drinker, moderate drinker, or abstainer) was used as the outcome variable. A multinomial logistic regression model was used, and an analysis comparing heavy drinkers and abstainers, as well as moderate drinkers and abstainers, was conducted. Results Moderate drinking was positively associated with high educational level or high household income for men and women, as well as married status for men. In addition, unemployment was found to be negatively associated with heavy drinking for men and women, and an unmarried status was also found to be negatively associated with heavy drinking for men. Moreover, lower educational levels and smoking prevalence were found to be associated with heavy drinking for men and women. Furthermore, living alone for men and working in a large-scale company for women were also found to be predictors of heavy drinking. Conclusions The preventive measures for heavy drinking were suggested to be particularly needed for those with lower educational levels and smokers. A call for attention among men living alone and among female employees in large-scale workplaces is also needed.